Evidence for high-fidelity timing-dependent synaptic plasticity of human motor cortex - Cash, R. F. H.; Mastaglia, F. L.; Thickbroom, G. W. (Journal of neurophysiology, 2013)
A single transcranial magnetic stimulation (TMS) pulse typically evokes a short series of spikes in corticospinal neurons [known as indirect (I)-waves] which are thought to arise from transynaptic input. Delivering a second pulse at inter-pulse intervals (IPIs) corresponding to the timing of these I-waves leads to a facilitation of the response, and if stimulus pairs are delivered repeatedly, a persistent LTP-like increase in excitability can occur. This has been demonstrated at an IPI of 1.5 ms, which corresponds to the first I-wave interval, in an intervention referred to as ITMS (I-wave TMS), and it has been argued that this may have similarities with timing-dependent plasticity models. Consequently, we hypothesized that if the second stimulus is delivered so as not to coincide with I-wave timing, it should lead to LTD. We performed a crossover study in 10 subjects in which TMS doublets were timed to coincide (1.5-ms IPI, ITMS 1.5 ) or not coincide (2-ms IPI, ITMS 2 ) with I-wave firing. Single pulse motor-evoked potential (MEP) amplitude, resting motor threshold (RMT), and short-interval cortical inhibition (SICI) were measured from the first dorsal interosseous (FDI) muscle. After ITMS 1.5 corticomotor excitability was increased by ∼60% for 15 min ( P < 0.05) and returned to baseline by 20 min. Increasing the IPI by just 500 μs to 2 ms reversed the aftereffect, and MEP amplitude was significantly reduced (∼35%, P < 0.05) for 15 min before returning to baseline. This reduction was not associated with an increase in SICI, suggesting a reduction in excitatory transmission rather than an increase in inhibitory efficacy. RMT also remained unchanged, suggesting that these changes were not due to changes in membrane excitability. Amplitude-matching ITMS 2 did not modulate excitability. The results are consistent with timing-dependent synaptic LTP/D-like effects and suggest that there are plasticity mechanisms operating in the human motor cortex with a temporal resolution of the order of a few hundreds of microseconds.